ENTREPRENEURS’ AND CUSTOMERS’ ENGAGEMENT TOWARDS ONLINE VIDEO-BASED TRAINING AND ADVERTISEMENT - Mariani Mohd. Dahlan (International Journal of Accounting, Finance and Business, 2022)
This research emerged from the researcher’s concern and reviews on the weaknesses of the Bumiputera SME entrepreneurs in marketing and network business. The purpose of this research is to explore the entrepreneurs’ and customers’ engagement towards online video-based training. The participants were chosen from the new MARA Small Medium Enterprises (SMEs) in Perak and the chosen research method was a mixed-method sequential explanatory design involving quantitative and qualitative methods. The independent variables were video-based Facebook training (vFB-Ads) and FB Advertisement (FB Ads). The dependent variables involved the entrepreneurs’ learning engagement, customers’ engagement of the vFB-Ads and FB Ads. A total of 31 entrepreneurs were randomly sampled from MARA Negeri Perak. The data obtained were analysed by carrying out descriptive and inferential statistics, as well as thematic analysis. The findings obtained from the analysis of the entrepreneurs’ learning engagement towards vFB-Ads revealed that they indicate the emotional, behavioural and cognitive engagement towards vFB-Ads. The findings also revealed that all of customers were satisfied with the FB Ads. Also, two barriers or limitations in using FB Ads for marketing and creating a business network were identified namely, A Strict FB Ads Rule and Lack of FB Ads Guide. Advertising on FB was also affecting the entrepreneurs’ business in terms of marketing and their business network. In addition, vFB-Ads assists entrepreneurs how to advertise on FB paving the way for business network and customer relationship building.